Intracranial stenosis, cerebrovascular diseases, and cognitive impairment in chinese - Hilal, Saima; Saini, Monica; Tan, Chuen Seng; Catindig, Joseree A; Dong, Yan Hong; Holandez, Rachelle L; Niessen, Wiro J; Vrooman, Henri A; Ting, Eric; Wong, Tien Yin; Chen, Christopher; Venketasubramanian, Narayanaswamy; et al. (Alzheimer disease and associated disorders, 2015)
Extracranial carotid artery disease has been shown to be related to cognitive deficits. However, limited data are available on intracranial stenosis (ICS) and cognitive impairment. We investigate the association between ICS and cognitive impairment in Chinese. Subjects (n=278), recruited from the Epidemiology of Dementia in Singapore Study, underwent comprehensive clinical evaluation, neuropsychological testing, and brain magnetic resonance imaging (MRI), including 3-dimensional-time-of-flight magnetic resonance angiography (MRA). Cognitive function was expressed as composite and domain-specific Z-scores. Cognitive impairment no dementia and dementia were diagnosed according to internationally accepted diagnostic criteria. Linear and logistic regression models were adjusted for age, sex, education, vascular risk factors, and other MRI markers. A total of 29 (10.4%) persons had ICS on MRA, which was significantly associated with both composite cognitive Z-scores [mean difference in Z-score, presence vs. absence of ICS: -0.37 (95% confidence interval: -0.63, -0.12)] and specific domains including executive function, language, visuomotor speed, verbal memory, and visual memory. ICS was also related to significant cognitive impairment (odds ratio: 5.10 [1.24 to 21.02]). With respect to other MRI markers, adjusted for the presence of lacunar infarcts, the associations of ICS with both composite and domain-specific Z-scores, and significant cognitive impairment became nonsignificant; however, adjustment for other MRI markers did not alter these associations. In this Chinese population, presence of ICS was associated with cognitive impairment independent of vascular risk factors. These associations may be mediated through the presence of infarcts.